Strategi Komunikasi Pemasaran UMKM di Bidang Makanan dan Minuman melalui Media Sosial Instagram di Tengah Pandemi Covid-19 di Indonesia - Fawwaz Fawwaz; Roswita Oktavianti (Kiwari, 2022)
Early 2020 was the beginning of a tough year for micro, small and medium enterprises (MSMEs) in Indonesia, one of which was Sushi Komura who was the subject of research in this study. Sushi Komura is a food outlet that sells Japanese specialties, namely sushi. Due to the Covid-19 that occurred, this had an impact on the sales of Sushi Komura. Marketing communications combined with marketing strategies and efforts to build positioning are carried out by many MSMEs so that sales continue to increase amid the Covid-19 conditions. To do this, of course, the company needs to identify the position of competitors who can determine the direction of the strategic position in building a positioning in the midst of business competition to attract consumer interest. Social media has an important role in building positioning activities for Sushi Komura SMEs. One of the things that need to be considered from using social media as a marketing medium and also building positioning is how the content can be of interest and liked by the audience, because if it is appropriate and appropriate, it can be an advantage for companies to attract buyers. The theory that helps this research is the theory of marketing communication strategy and positioning theory. The results of the findings of this study are that social media and also the application of cleanliness are the main keys for MSMEs to increase their selling power, besides that applying the right marketing strategy is also a determining factor for MSMEs to survive in the midst of the Covid-19 pandemic.Awal tahun 2020 lalu menjadi awal tahun yang berat bagi pelaku usaha mikro, kecil dan menengah (UMKM) di Indonesia, salah satunya Sushi Komura yang menjadi subyek penelitian pada penelitian ini. Sushi Komura merupakan gerai makanan yang menjual makanan khas Jepang yakni sushi. Akibat Covid-19 yang terjadi, hal ini berdampak terhadap penjualan Sushi Komura. Komunikasi pemasaran yang dipadukan dengan strategi pemasaran serta usaha membangun positioning dilakukan oleh banyak UMKM agar penjualan tetap meningkat ditengah kondisi Covid-19. Untuk menjalankan hal tersebut tentunya perusahaan perlu mengidentifikasi posisi pesaing yang dapat menentukan arah strategi dalam membangun positioning ditengah persaingan usaha untuk menarik minat konsumen.  Media sosial memiliki peranan yang penting dalam kegiatan membangun positioning bagi UMKM Sushi Komura. Salah satu hal yang perlu diperhatikan dari penggunaan media sosial sebagai media pemasaran dan juga membangun positioning adalah bagaimana konten tersebut dapat diminati dan disukai oleh khalayak, karena apabila sudah sesuai dan tepat dapatlah menjadi keunggulan bagi perusahaan untuk menarik minat pembeli. Teori yang membantu  penelitian ini adalah teori strategi komunikasi pemasaran. Hasil dari temuan penelitian ini bahwa media sosial dan juga penerapan kebersihan menjadi kunci utama bagi UMKM untuk meningkatkan daya jual, selain itu menerapkan strategi pemasaran yang tepat juga menjadi faktor penentu bagi UMKM untuk bertahan di tengah pandemi Covid-19.